Peran Pemuda dalam Mengimplementasikan Nilai Nilai Toleransi Antarumat Beragama: Studi Kasus Komunitas Islam dan Kristen di Desa Bucu, Kembang Jepara - Fuad Fahmiy; Fathur Rohman (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research is motivated by the importance of strengthening interreligious tolerance in Indonesia’s multicultural society, with a focus on Bucu Village, located in Kembang Sub-district, Jepara Regency, which is known for its ability to maintain harmony between Muslim and Christian communities. The aim of this study is to examine how the youth in the village implement and internalize the values of tolerance, as well as to identify the supporting and inhibiting factors of these efforts. This research employs a qualitative approach using a case study method. Data collection techniques include observation, in-depth interviews with religious leaders, youth, and community members, as well as documentation. The findings reveal that tolerance in Bucu Village has become institutionalized in the residents’ daily lives, especially among the younger generation. The implementation of tolerance is reflected in the unity displayed during village activities, mutual respect for interfaith worship practices, and the organization of inclusive communal events. These values have been internalized from an early age through family upbringing and social environments. The main supporting factors include collective awareness, the role of community leaders, fair village leadership, and routine social interactions involving all groups. Challenges include persistent social stereotypes, feelings of marginalization among minority groups, and the influence of intolerant ideologies through social media. Solutions are pursued through strengthening interfaith communication, digital education, and the development of inclusive social activities. Thus, the youth of Bucu Village have become key agents of tolerance and symbols of harmony in a diverse society.